UJI AKTIVITAS ANTIBAKTERI EKSTRAK METANOL RUMPUT LAUT (Eucheuma sp) PADA BERBAGAI TINGKAT KONSENTRASI TERHADAP PERTUMBUHAN BAKTERI Escherichia coli DAN Staphylococcus aureus - Indria Hafizah; Nur Illiyin Akib; Muhammad Fajrianto (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2014)
Red algae seaweed Eucheuma sp containflavonoids compound which has activity as anantibacterial. Thisstudyaimstodeterminethe difference of seaweed methanol extract(Eucheuma sp) on inhibiting the growth ofEscherichia coli andStaphylococcus aureusbacteria. This research was conducted with post–test only design (one-shot case study) with a variable treatment of theseaweed methanolextract (Eucheuma sp) against S. aureus and E. coli.Extractswerethendividedinto 5 concentration of 75%, 50%, 25%, 5%, and non-extraction (squeezed). Analysis of data t odetermine the level of concentration differences seen from the ANOVA test (analysis of variance) followedby a posthoc test. The results of bivariat analysis showed the inhibition of E. coli bacteria there are difference in clear zone diameter which are significant various levels of each concentration, with a value of p = 0.000(p < 0.05) and in S. Aureus inhibition P = 0.073 (p > 0.05) which means there is no difference in the diameter of clear zone at various levels for each concentration. The conclusions of this research are differences extract concentration have effect on the inhibition of the growth of the bacterium Escherichia coli and the difference in concentration of the extract have no effect on the inhibition of growth of Staphylococcus aureus.Key words : Eucheuma sp, Escherechia coli, Staphylococcus aureus